Preeclampsia is a risk factor for Low Birth Weight (LBW) infants - Indriany, Daffina Syazah; Yorita, Epti; Ekanugraheni, Diah; Yanniarti, Sri (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Infant mortality remains high and is more common in the neonatal period. Causes of neonatal death include asphyxia, sepsis, infection and LBW(LBW) in preterm and term infants. One of the factors influencing the incidence of LBW is pre-eclampsia. This is because pre-eclampsia affects the utero-placental circulation so that it affects the delivery of nutrients to the fetus, resulting in fetal nutrient deprivation and intrauterine growth restriction. Objectives: This study aims to assess the relationship between pre-eclampsia and the incidence of LBW in the Mawar Room of Dr M. Yunus Bengkulu Hospital. Methods: This study used a case-control design. The sample was all babies born in M Yunus Hospital in the years 2019-2022.The case group were LBWbabies and the control group were normal birth weight babies. The total sample size was 128 with a ratio of 1:1. Samples were collected using purposive sampling with inclusion criteria of babies born alive with complete medical records. Data analysis in this study used univariate analysis to view frequency distribution, bivariate with chi-squared test and multivariate with logistic regression using SPPS software version 24. Results: The incidence of pre-eclampsia was 13.3%, 34% age at risk, parity 37.5% garande multipara, 4imipara and multipara and most (62.5%) had primary education 47.5%. There is an association of pre-eclampsia with the incidence of LBW. There is an association of age, parity and education with the incidence of LBW, but pre-eclampsia is the most dominant factor that is the most dominant risk variable that affects the incidence of LBW. Conclusions: There is an association between pre-eclampsia, age, parity and education with the incidence of LBW. Pre-eclampsia is the most dominant factor in the incidence of LBW.